Beliefs System and its Relationship to Sports Prejudice among Soccer Fans - Sami Hameed, Omar; Al-Daghistani, Sanaa Issa Mohammed (Al-Adab Journal, 2020)
the format of beliefs (Belief system), which means the layout of rigid beliefs among individuals, the controlling view of life, and the lack of tolerance for those who differ from us in ideas and opinions, i.e. that everyone has a cognitive structure and his own beliefs about political and social life that are organized in a holistic pattern, which works on creating a cognitive system consisting of diverse beliefs, attitudes and preferences, it is described on two poles, one of which is closed, characterized by stagnation and another flexible, characterized by openness, and on this basis it can be said that people with closed minds are those who reject new ideas even if they are supported by strong evidence and cling to their old beliefs, while individuals are open Mindfulness are those who accept new ideas and receive new beliefs, especially if they are supported by evidence. In order to achieve the aims of the current research, the researcher adopted the theory of belief formations of (Rokeach ,2015), in the beliefs system theory, and the researcher prepared a scale of beliefs form after reviewing the approved theory and previous standards. And the preparation of the sports prejudice scale after reviewing the social learning theory and previous studies, and the researcher undertook the procedures for analyzing the paragraphs on the research scale, as well as the validity was extracted using the exploratory factor analysis of sports beliefs and sports prejudice. Reliability of the scale of beliefs (0.84) using the Alpha Cronbach method.